COMPARATIVE ANALYSIS OF EMPLOYEE SATISFACTION LEVELS PTPN IV REGIONAL I MEDAN AFTER HOLDINGISAS - Afzalia; Harmein Nasution; Yeni Absah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study analyzes employee satisfaction after holding at PTPN IV Regional I Medan. The population of this study consisted of 682 employees, with a sample of 87 respondents selected using the Slovin formula. Data were collected through a questionnaire with a Likert scale and secondary data were taken from written reports on the condition of the company's office. The study results showed an increase in job satisfaction after holding, especially in the variables of job content, supervision, opportunities for advancement, salary/incentives, and relationships with coworkers. However, there was no increase in the working conditions variable. The results of the hypothesis test showed a significant difference in the level of employee satisfaction after holding. The recommendations of this study emphasize the importance of paying attention to job content, improving supervision, providing opportunities for career advancement, fair treatment, open communication, and supportive office facilities. Holdingization causes organizational changes that affect job satisfaction. The higher the level of satisfaction, the better the employee performance. This study distinguishes between the levels of satisfaction before and after restructuring.